IMPLEMENTASI STRATEGI PROJECT BASED LEARNING (PjBL) DALAM PEMBELAJARAN PIDATO BAHASA INDONESIA DI MTs NEGERI 3KOTA JAMBI - Nabila Syakila; Nur Alimi; Helty; Liza Septa Wilyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of Project Based Learning (PjBL) strategy in Indonesian language learning on speech material at class VIII.1 MTs Negeri 3 Kota Jambi. This research used qualitative descriptive method through field observation on May 19, 2026. Data were collected through observation, field notes, and interviews with the Indonesian language teacher. The results showed that the teacher applied PjBL strategy by dividing students into heterogeneous groups, giving freedom to explore references through gadgets and school libraries, and assessing student competence through speech performance assessment. The learning process ran well and interactively, although time management constraints were found. The application of PjBL in this study is in line with the principle of student-centered learning which effectively stimulates higher-order thinking skills (HOTS) and active student involvement. The use of PPT media and authentic evaluation also supported the achievement of learning objectives comprehensively. It is recommended that future learning pay more attention to time allocation and the use of more varied interactive digital media.